2012
DOI: 10.4100/jhse.2012.73.07
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between out-of-school sport participation and positive youth development

Abstract: Carreres-Ponsoda F, Escartí A, Cortell-Tormo JM, Fuster-Lloret V, Andreu-Cabrera E. The relationship between out-of-school sport participation and positive youth development. J. Hum. Sport Exerc. Vol. 7, No. 3, pp. 671-683, 2012. Despite growing evidence that participation in out-of-school activities and especially physical activity and sport programs facilitates positive development, little developmental research has been conducted on out-of-school sports programs compared with no participation in these acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 25 publications
0
28
0
7
Order By: Relevance
“…Other authors, (Carreres-Ponsoda, Escartí, Cortell-Tormo, Fuster-Lloret, & Andreu-Cabrera, 2012) have shown that teenagers who practise sport in extracurricular timetable reveal significantly higher self-efficacy levels, prosocial behaviour and personal and social responsibility than other same-age subjects who spend their free time doing other type of activity or than those who do not practise any extracurricular activity.…”
Section: Introductionmentioning
confidence: 93%
“…Other authors, (Carreres-Ponsoda, Escartí, Cortell-Tormo, Fuster-Lloret, & Andreu-Cabrera, 2012) have shown that teenagers who practise sport in extracurricular timetable reveal significantly higher self-efficacy levels, prosocial behaviour and personal and social responsibility than other same-age subjects who spend their free time doing other type of activity or than those who do not practise any extracurricular activity.…”
Section: Introductionmentioning
confidence: 93%
“…Studies included in our review showed consistent relationships between sport participation and both self-esteem (Babiss & Gangwisch, 2009 ; Barber et al, 2001 ; Carreres-Ponsoda et al, 2012 ; Harrison & Narayan, 2003 ; Marsh & Kleitman, 2003 ; Papacharisis et al, 2005 ) and sense of personal control or mastery (Durlak et al, 2010 ; Gould et al, 2012 ; Marsh & Kleitman, 2003 ). All of these studies used survey-based designs to examine the association between sport participation and self-esteem, mastery, or sense of personal control.…”
Section: Resultsmentioning
confidence: 53%
“…Alguns têm reforçado os benefícios que as experiências esportivas podem proporcionar aos jovens, nos aspectos físicos, cognitivos, emocionais e sociais 3,4 , enquanto outros tem apresentado indicativos de experiências negativas nos mesmos domínios do desenvolvimento 5,6 . Essas diferenças ocorrem devido às inúmeras variáveis empregadas nos estudos 7,8 , as quais parecem ser influenciadas pela abordagem teórica utilizada 9 .…”
Section: Introductionunclassified